Ibuprofen use is associated with reduced C-reactive protein and interleukin-6 levels in chronic spinal cord injury. (2nd January 2022) - Park, Andrew; Anderson, Dustin; Battaglino, Ricardo A.; Nguyen, Nguyen; Morse, Leslie R.
Abstract : Objective: To assess the association between ibuprofen use and the systemic inflammatory biomarkers C-reactive protein (CRP) and interleukin-6 (IL-6) in chronic Spinal Cord Injury (SCI). Study design: Prospective cohort study. Setting: Community dwelling individuals with SCI. Participants: 338 (278 male, 60 female) community dwelling individuals with chronic SCI (≥1-year post-injury). Interventions: None. Main outcome measures: CRP and IL-6 levels were quantified by ultra-sensitive ELISA assay. General linear models were used to assess associations between various clinical and demographic factors and CRP and IL-6 levels. Results: There were 50 active ibuprofen users and 288 non-users. After adjusting for clinical and demographic factors, ibuprofen users had significantly lower CRP levels (2.3 mg/L versus 3.5 mg/L, P = 0.04) and IL-6 levels (3.2 pg/ml versus 4.0 pg/ml, P = 0.04) compared to nonusers. Conclusions: Our study suggests that self-reported ibuprofen use may be negatively associated with CRP and IL-6 levels in chronic SCI after adjusting for known confounding factors, and suggests ibuprofen use may be an important, potential variable to consider in future studies focused on systemic inflammation in SCI. Future prospective studies require assessing frequency, duration, and dosage-dependent effects of ibuprofen on systemic markers of inflammation in chronic SCI. These findings may support future clinical trials to determine safety and efficacy of ibuprofen treatment for various outcomes in chronic SCI.